Immunovirotherapy Based on Recombinant Vesicular Stomatitis Virus: Where Are We? - Zhang, Yuguo; Nagalo, Bolni Marius (Frontiers in Immunology, 2022)
Vesicular stomatitis virus (VSV), a negative-strand RNA virus of the Vesiculovirus genus, has demonstrated encouraging anti-neoplastic activity across multiple human cancer types. VSV is particularly attractive as an oncolytic agent because of its broad tropism, fast replication kinetics, and amenability to genetic manipulations. Furthermore, VSV-induced oncolysis can elicit a potent antitumor cytotoxic T-cell response to viral proteins and tumor-associated antigens, resulting in a long-lasting antitumor effect. Because of this multifaceted immunomodulatory property, VSV was investigated extensively as an immunovirotherapy alone or combined with other anticancer modalities, such as immune checkpoint blockade. Despite these recent opportunities to delineate synergistic and additive antitumor effects with existing anticancer therapies, FDA approval for the use of oncolytic VSV in humans has not yet been granted. This mini-review discusses factors that have prompted the use of VSV as an immunovirotherapy in human cancers and provide insights into future perspectives and research areas to improve VSV-based oncotherapy.